Joint Econometric Analysis of Temporal and Spatial Flexibility of Activities, Vehicle Type Choice, and Primary Driver Selection. Issue 1 (January 2015) - Anowar, Sabreena; Eluru, Naveen; Miranda-Moreno, Luis F.; Lee-Gosselin, Martin
This study examined the relationship between four individual-level travel choice processes of daily activity: spatial flexibility of the activity, temporal flexibility of the activity, vehicle choice for the activity, and primary driver (for auto users). Activity flexibility (spatial and temporal) has been suggested as a precursor to the travel pattern observed for an activity. This study examined the impact of activity flexibility through unique data drawn from Quebec City, Quebec, Canada from 2003 to 2006. In traditional literature on travel behavior, vehicle fleet decisions have been examined as a long-term choice with annual usage metrics. However, the long-term vehicle usage observed (as studied in the literature) is an aggregation of the household's yearly vehicle type and usage behavior. Only recently have researchers begun to consider decisions about vehicle usage (type and mileage) as a short-term decision in travel behavior models. By examining short-term vehicle usage, this study explored, at a disaggregate level, the interaction of activity behavior (defined as flexibility) and vehicle type choice. A panel mixed multinomial logit model was applied to analyze the four choices within the decision process to account for the intrinsic unobserved taste preferences across individuals. The analysis results revealed that several individual and household sociodemographic characteristics, residential location, and activity attributes, as well as contextual variables, influenced the packaged choice of temporal flexibility, spatial flexibility, vehicle type choice, and primary driver selection. The presence of common unobserved correlation across various alternatives was also incorporated.